Возрастная структура популяции черных стрижей (Apus apus) в Окском заповеднике - Кашенцева, Т.А. (Вестник зоологии, 1982)
667 swift individuals were ringed in the Oka reservation during 1950-1979 with subsequent recapture o1 318 individuals. The Der cent index or return to the colony fOr birds ringed both young and adult is found to be 4.1 and 40.1, respectively. Mortality In adult ringed birds reached 24.4%, average liletime 3.0 years, maximal age- I years The most numerous group consisted of four-year birds starting reproduction. The young dispersion degree at the survival rate 66.% 18 80%.